Improving Students’ Higher Order Thinking Skills through Portfolio Assessment on Biology Curriculum and Textbook Analysis Course - Yosi Laila Rahmi; Heffi Alberida (Bioeducation Journal, 2017)
Curriculum occupies a central position in education. Curriculum changes guided by the times and technology. The main problems of implementation of curriculum change is to change the mindset of teachers. Prospective teachers should have high order thinking skills to face the times and technology. One of efforts could be made a lecturer for conditioning of learning to be able to develop higher order thinking skills of students by using the right assessment. One assessment that play a role in increasing the skills of thinking is portfolio assessment. This study aims to describe the increase in high order thinking skills of students applying portfolio assessment. This research is a classroom action research conducted on students who take courses in curriculum and biology textbook in biology Faculty UNP in the July to December semester of 2017. The results showed an increase in high order thinking skills of students using portfolio assessment.